High-Temperature Processing and Recovery of Cu Catalyst Promoter - Čarnogurská, Mária; Lázár, Marián; Příhoda, Miroslav; Skočilasová, Blanka; Kurilla, Peter; Marek, Jiří (Manufacturing Technology Journal, 2018)
The following article describes the results obtained from the plasma smelting reduction of a particular type of waste - catalyst with a Cu promoter. The catalyst is used for the process of a selective reduction of nitrobenzene (C6H5NO2) to aniline (C6H5NH2). The plasma smelting occurs in a reducing atmosphere. Six samples of the exhausted catalyst with a Cu promoter were used in the smelting process. The chemical composition of the promoter exhibited a presence of a wide range of elements. Fluorspar (fluorite) and calcium oxide (quicklime) were used as the slag-agent for the given testing. Reducing agent was the powdery graphite - waste from the manufacture of the graphite semi-finished product. The results of experiments, carried out at 80 kVA in the plasma reactor, proved that this type of catalyst can be, in fact, disposed of using the plasma technology. Recyclability of the metal contained in this waste is high; Cu ranges around 88%. Moreover, the article describes the chemical analysis of the slag, fly ash and the composition of synthesis gas in all samples of the processed catalyst.
Keywords: Waste; Catalyser; Cu promoter; Plasma technology